vertex (3, 1)
directrix y = 6
The equation of a parabola is
![y=(1)/(4(f-k))(x-h)^2+k](https://img.qammunity.org/2023/formulas/mathematics/college/unuvxaznisilrudin3ykgfcf7eylgy3159.png)
where,
(h,k) is the vertex and (h,f) is the focus
Thus,
h = 3
k = 1
The distance from the focus to the vertex is equal to the distance from the vertex to the directrix, then f - k = k - 6
replace k=1 and solve for f,
![\begin{gathered} f-1=1-6 \\ f=-5+1 \\ f=-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ym1cpx8qjm24wrlf869csrq41pz7bg4vi2.png)
Thus,
h = 3
k = 1
f = -4
therefore, the equation of the parabola is,
![\begin{gathered} y=(1)/(4*(-4-1))(x-3)^2+1 \\ \\ y=-(1)/(20)(x-3)^(2)+1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/l8ly6ye6jha0cbq5hux73tivtap5st6gy1.png)